Performance management in the public sector - Dooren, Wouter van; Bouckaert, Geert; Halligan, John (Routledge masters in public management series., 2026)
"This fully revised third edition provides a comprehensive exploration of performance management in the public sector, incorporating nearly 200 new references from the latest decade of performance management research. The book presents fresh evidence on the uses and effects of performance management, making it an essential resource for students, researchers, and professionals seeking to design functional performance management systems. Moving beyond the traditional New Public Management paradigm, the book critically examines how performance measurement, incorporation, and use can be purposefully designed to enhance public management and governance. With a strong didactical focus, it offers guidance on designing performance management systems that align with contemporary challenges and policy needs. Readers will benefit from a structured approach that combines theoretical insights with practical applications and cases. Whether in academia, government, or consultancy, this book equips readers with the knowledge and tools to measure and manage performance effectively"-- Provided by publisher.